Simulation as a set-up for technical proficiency: can a virtual warm-up improve live fibre-optic intubation? - Samuelson, S. T.; Burnett, G.; Sim, A. J.; Hofer, I.; Weinberg, A. D.; Goldberg, A.; Chang, T. S.; DeMaria, S. (British journal of anaesthesia : BJA, 2016)
Abstract Background Fibre-optic intubation (FOI) is an advanced technical skill, which anaesthesia residents must frequently perform under pressure. In surgical subspecialties, a virtual ‘warm-up’ has been used to prime a practitioner's skill set immediately before performance of challenging procedures. This study examined whether a virtual warm-up improved the performance of elective live patient FOI by anaesthesia residents. Methods Clinical anaesthesia yr 1 and 2 (CA1 and CA2) residents were recruited to perform elective asleep oral FOI. Residents either underwent a 5 min, guided warm-up (using a bronchoscopy simulator) immediately before live FOI on patients with predicted normal airways or performed live FOI on similar patients without the warm-up. Subjects were timed performing FOI (from scope passing teeth to viewing the carina) and were graded on a 45-point skill scale by attending anaesthetists. After a washout period, all subjects were resampled as members of the opposite cohort. Multivariate analysis was performed to control for variations in previous FOI experience of the residents. Results Thirty-three anaesthesia residents were recruited, of whom 22 were CA1 and 11 were CA2. Virtual warm-up conferred a 37% reduction in time for CA1s (mean 35.8 ( sd 3.2) s vs . 57 ( sd 3.2) s, P <0.0002) and a 26% decrease for CA2s (mean 23 ( sd 1.7) s vs . 31 ( sd 1.7) s, P =0.0118). Global skill score increased with warm-up by 4.8 points for CA1s (mean 32.8 ( sd 1.2) vs . 37.6 ( sd 1.2), P =0.0079) and 5.1 points for CA2s (37.7 ( sd 1.1) vs . 42.8 ( sd 1.1), P =0.0125). Crossover period and sequence did not show a statistically significant association with performance. Conclusions Virtual warm-up significantly improved performance by residents of FOI in live patients with normal airway anatomy, as measured both by speed and by a scaled evaluation of skills.